Assessing the needs of critically-ill patients confined in the ICU of Maharaj Nakorn ChiangMai Hospital - Chaweewan, Tongchai
Each individual has his own needs which become more complex when he is ill and are intensified during crisis situation. It is very important for nurses to know critically-ill patients needs in order to improve the quality of nursing care. This study aims to determine critically-ill patients' needs and its relationship with socio-demographic variables. The locale used in this study is the Surgical and Medical Intensive Care Unit of Marajah Nakorn Chiang Mai Hospital in Thailand. The respondents consisted of patients who were confined in both ICUs during October 17, 1986 to January 2, 1987. The conceptual framework was based on Maslow's hierarchy of human needs. The hypotheses were organized according to the framework and the objectives of the study to see the difference in the level of physiological, psychosocial and spiritual needs. The variables studied are the type of ICU, age, sex, civil status, education, occupation, and patients' diagnosis. The instruments used in this study consisted of 4 parts. They are in the forms of socio-demographic data sheet, physical assessment form, open-ended and checklist question and a rating-scale statements. Implications show the importance of psychosocial and spiritual support which should be provided to critically-ill patients as well as the physiological care. It should be realized that once the physiological needs are partially met, the psychosocial and spiritual needs become stronger. More attention should be paid on the older, the lower educated patients, the jobless and the agricultural workers. Recommendations point out an awareness to the nursing educators, staff nurses, nursing services, administrators and patients' families to realize the importance of psychosocial and spiritual needs as well as physiological needs of critically-ill patients, and how these needs should be met in order to obtain a high quality nursing care.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Intensive care nursing; Critically ill patients